Sunday, February 19, 2012

Calculus: Implicit Differentiation

From this video, I found it very easy to understand.







Staring 07:23, he use the formula of "Point-Slope Equation of a Line", which is "y - y1 = m(x - x1)".

So y1 = -1, x1 = 1, m = -1 [the result from the derivative using implicit differentiation] so,

y - y1 = m(x - x1)

y - -1 = m(x - 1)

y + 1 = -1 (x -1)

y = -x + 1 - 1
y = -x


Note that, Point-Slope Equation of a Line is different from Equation of a Straight Line formula.
        

No comments: